2016
DOI: 10.1021/acs.jpcc.6b04798
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Studies on RE2Hf2O7:5%Eu3+ (RE = Y, La, Pr, Gd, Er, and Lu) Nanoparticles: Effects of the A-Site RE3+ Cation and Calcination on Structure and Photoluminescence

Abstract: A series of 5mol% Eu 3+ doped rare earth (RE) hafnium oxide RE 2 Hf 2 O 7 (RE = Y, La, Pr, Gd, Er, and Lu) nanoparticles (NPs) have been synthesized, calcinated, and systematically investigated using X-ray diffraction (XRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), and optically excited luminescence. Effects of the A-site RE 3+ cation and calcination on the crystal structure of the RE 2 Hf 2 O 7 :5%Eu NPs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 48 publications
4
55
0
Order By: Relevance
“…5) and those of the II – IV centers. Next, the absence in the Raman spectra of the strongest characteristic phonon mode of stannate pyrochlore (around 510 cm −1   67 ) along with the strongly dissimilar emission exhibited by Eu 2 Sn 2 O 7 6870 grown by us using a sol-gel method 71 (also included in Fig. 5 as orange spectrum) to Eu centers II – IV dismiss the occurrence of this phase in our samples.…”
Section: Resultsmentioning
confidence: 75%
“…5) and those of the II – IV centers. Next, the absence in the Raman spectra of the strongest characteristic phonon mode of stannate pyrochlore (around 510 cm −1   67 ) along with the strongly dissimilar emission exhibited by Eu 2 Sn 2 O 7 6870 grown by us using a sol-gel method 71 (also included in Fig. 5 as orange spectrum) to Eu centers II – IV dismiss the occurrence of this phase in our samples.…”
Section: Resultsmentioning
confidence: 75%
“…These properties make them suitable for scientific and technological applications such as thermal barrier coatings, 1 magnetic materials, 2,3 electrocatalysis, 4,5 sensors, 6 optical materials, 7 solid-oxide fuel cells, 8 high level nuclear waste hosts, 9 etc. Moreover, recently relevant nanostructured pyrochlore materials have gained significant attention compared with their bulk counterparts in the areas of photoluminescence, [10][11][12][13] scintillation, [11][12][13] and magnetism. 14 In this context, La 2 Zr 2 O 7 and La 2 Hf 2 O 7 have been two standout pyrochlores for their suitability in various kinds of technological applications such as luminescence, scintillator, ferroelectric material, nuclear waste host, catalyst, and electrode material in fuel cells, etc.…”
Section: Introductionmentioning
confidence: 99%
“…34 There are only a few independent reports on the luminescence studies of La 2 X 2 O 7 :Eu 3+ (X = Zr and Hf), but comparative studies for the observed differences are missing, not to mention the understanding of the underlying mechanisms both experimentally and theoretically, including the energetics of ionized oxygen vacancies, the host to dopant energy transfer, and non-radiative channels. [10][11][12]22,23 Doping host materials is an efficient way to synthesize tunable luminescent phosphors. Moreover, doping can shift the light emission from undoped La 2 B 2 O 7 (B = Zr and Hf) NPs to other regions.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of nanomaterials is ultimately governed by the melting point of salts used as molten solvents, such as alkali chloride, sulfate, carbonate, or hydroxide 1,6,31,32 . It has been reported that the use of different molten salts can modify the formation temperature, thereby altering the particle size and morphology 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Generalizability: The MSS method is also a generalizable technique to produce nanoparticles with various compositions. Other than simple metal oxides and some fluorides, nanomaterials of complex metal oxides that have been successfully synthesized by the MSS method include perovskites (ABO 3 ) 10,11,12,13,14 , spinel (AB 2 O 4 ) 15,16 , pyrochlore (A 2 B 2 O 7 ) 4,17,18,19 , and orthorhombicstructures (A 2 B 4 O 9 ) 2,3,20 . More specifically, these nanomaterials include ferrites, titanates, niobates, mullite, aluminium borate, wollastonite, and carbonated apatite 7,9,21 .…”
Section: Introductionmentioning
confidence: 99%